Lipid Metabolic Process Involved in Oocyte Maturation During Folliculogenesis - Liu, Tao; Qu, Jiangxue; Tian, Mengyuan; Yang, Rui; Song, Xueling; Li, Rong; Yan, Jie; Qiao, Jie (Frontiers in Cell and Developmental Biology, 2022)
Lipid is the main energy storage and its metabolites act as important bioactive materials in mammalian follicles. Triglycerides in cumulus-oocyte complexes (COCs) break down into fatty acids and further produce ATP by β-oxidation and oxidative phosphorylation under the induction of luteinizing hormone surge, providing enough energy for oocyte maturation and embryo development. Cholesterol is the precursor of sex steroid hormones in granulosa cells and theca cells and several intermediates during steroidogenesis, like the follicular fluid meiosis-activating sterol, can promote oocyte to resume meiosis and acquire developmental competence. Lipoproteins, the main carriers of cholesterol and triglycerides in blood circulation, are involved in follicular cholesterol homeostasis and oocyte meiosis. Scavenger receptor class B type I (SCARB1) mediate the selective intake of cholesterol and triglycerides in lipoproteins. However, the association between circulating high cholesterol and excess cholesterol in oocyte remains a mystery. This review describes the transcriptional expression patterns of several lipid metabolism-related genes in human oocyte and granulosa cells during folliculogenesis, which depict the spatiotemporal lipid metabolic changes in follicle and reveal the role of lipid metabolism on female reproductive capacity.